Ernest Hemingway the last interview and other conversations - Hemingway, Ernest 1899-1961 (Melville House, 2015)
"One of the twentieth century's most seminal literary icons reveals himself as never before in this wide-ranging collection of conversations from throughout his career, including his last"--Page 4 of cover
Keywords: Hemingway, Ernest / 1899-1961 / Interviews; Hemingway, Ernest / 1899-1961; Hemingway, Ernest -- 1899-1961; Geschichte 1900-2000; Authors, American / 20th century / Interviews; Journalists / United States / Interviews; Authors, American; Journalists; United States; USA; Interview